Analysis of the care of patients with Diabetes Mellitus and Hypertension: the experience of a small municipality in Brazil - Viegas Andrade, Monica (2019)
This article evaluates the care of a cohort of 260 individuals with diabetes and 295 individuals with hypertension before, during and after the implementation of the Innovative Care Laboratory for Chronic Conditions (LIACC). This intervention sought to strengthen Primary Health Care by implementing the Chronic Care Model in Santo Antônio do Monte, Minas Gerais, Brazil, between 2013 and 2014. This is a longitudinal observational study that uses clinical and laboratory information from medical records of patients with these two chronic conditions between 2012 and 2017. The outcomes evaluated were based on the guidelines of the Department of Health of Minas Gerais State. The results show the LIACC associated with the universalization of primary care macro-processes such as registration and classification of family risk. For patients with diabetes, there was an improvement in several markers in the period, such as increased consultation (from 90% in 2012 to 92% in 2017) and a decrease in patients with examinations outside the normal range. For individuals with hypertension, although there is a marked increase in medical appointments (from 80% in 2012 to 84% in 2017), clinical improvements were less evident. It can be concluded that LIACC is a promising intervention to improve the management of patients with chronic diseases in Primary Health Care.